Penyertaan Malaysia dalam perjanjian berkaitan kemapanan dan menangani bencana alam sekitar dalam pelbagai hala - Syed Hussain, Tuan Pah Rokiah; Ismail, Hamidi (2016)
Malaysia's participation in the various agreements relating to sustainability and addressing environmental disaster is a very good effort. For example, the Montreal Protocol is an agreement that has managed to gain international cooperation involving almost all countries in the world in addressing the global problem of ozone depletion that threaten human habitats and the global environment.Malaysia is one country in the world that is so active on the world stage in the realization of the desire to preserve the environment by adopting Multilateral Environmental Agreements (MEAs) at the national level. In addition, Malaysia is also active in the cooperation to deal with environmental disasters at international level for the benefit and safety of the world's population.These efforts show the role that Malaysia is committed in ensuring environmental sustainability and addressing environmental disasters that often occur within its boundaries.Malaysia's commitment and dedication in various efforts should be emulated by other countries of the world for the welfare of mankind.